Roderick M. Chisholm, The problem of the criterion, The Aquinas Lectures 1973, Marquette University Press, Milwaukee, 1973 - Argerami, Omar (1975)
Fil: Argerami, Omar. Universidad Nacional de La Plata; Argentina